Analisis Ketimpangan Fiskal di Provinsi Papua Tahun 2022-2025 - Agustina Sanggrangbano; Ida Ayu Purba Riani (Universitas Cenderawasih, 2026)
This study aims to analyze vertical and horizontal fiscal imbalances in Papua Province following the regional expansion (pemekaran) in 2022 across nine regencies and cities during the 2022-2025 period. The research employs a descriptive quantitative approach using data on Total Regional Revenue, Local Own-Source Revenue, and population. Vertical fiscal imbalance is measured using the VFI formula, while horizontal fiscal imbalance is measured using the Coefficient of Variation (CV) and Williamson Index (WI), which considers fiscal capacity and population weights. The results show that vertical fiscal imbalance is extremely severe, with the average VFI of Papua Province reaching 0.9792, while Keerom and Waropen Regencies reach 0.9948 and 0.9946 respectively, indicating almost total dependence on central government transfers. Horizontal fiscal imbalance is also very high, with CV values ranging from 150 percent to 248 percent and WI values ranging from 0.7461 to 0.8118, far exceeding the threshold for extreme inequality. Fiscal capacity of almost all regions is very low, with Jayapura City highest at 19.15 percent and Waropen lowest at 0.54 percent. The implication for the General Allocation Fund (DAU) is that the DAU no longer functions as an equalization tool but has become the main pillar of regional budgets due to extreme dependence, necessitating a reformulation of the DAU formula to be more favorable to low-capacity regions while adding incentive components for regions that successfully increase their Local Own-Source Revenue. Keywords: Vertical Fiscal Imbalance, Horizontal Fiscal Imbalance, Fiscal Capacity, General Allocation Fund